Tri-axial tactile sensing element. - Castellanos-Ramos, Julián; Navas-González, Rafael Jesús; Vidal-Verdú, Fernando (My University, 2013)
A 13 x 13 square millimetre tri-axial taxel is presented which is suitable for some medical applications. Finite Element Analysis is carried out to determine what structure is the best to obtain a uniform distribution of pressure on the sensing areas underneath the structure. This structure has been fabricated in plastic with a 3D printer and a commercial tactile sensor has been used to implement the sensing areas. A three axis linear motorized translation stage with a tri-axial precision force sensor is used to find the parameters of the linear regression model and characterize the proposed taxel. The results are analysed to see to what extent the goal has been reached in this specific implementation.
Keywords: Detectores; Método de los elementos finitos; Tactile sensor; Normal and tangential forces; FEA simulation